Ancient India - Green, Sara, 1964- (Ancient civilizations (Bellwether Media), 2020)
Explores the history of the ancient Indian civilization, discussing the Indians' rulers, daily life, and culture. Also describes the fall of the Indian empire. Includes a timeline, critical thinking questions, color photographs, a glossary, and further resources.